IBD MIMICS PRESENTED AT IBD LIVE: WHEN IT IS NOT INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Ward, Christopher; Shah, Samir; Farraye, Francis; Goyal, Alka; Hanson, John; Holubar, Stefan; Watson, Andrew; Wexner, Steven; Binion, David; Gaidos, Jill; Hull, Tracy; Al-Bawardy, Badr; et al.
Abstract: BACKGROUND: A group of Inflammatory Bowel Disease (IBD) specialists have been utilizing a weekly live video conference "IBD Live" to discuss multidisciplinary management of challenging cases. Since 2009 the conference has featured robust interactive case discussions among 150-200 gastroenterologists and colorectal surgeons from multiple academic institutions. Although the majority of cases presented are IBD, there have been a number of cases where IBD was not the ultimate diagnosis. Hence, we sought to characterize these "IBD mimics" to provide a structure for differential diagnosis. METHODS: All 106 hours of case conferences recorded and archived between May 2018 and June 2021 were reviewed. A total of 183 of the 215 cases discussed had an IBD diagnosis including 124 Crohn's disease (CD), 54 ulcerative colitis (UC) and 5 IBD unclassified. RESULTS: Many of the remaining 32 (14.9%) cases (Table 1) were referred to a specialist with a prior diagnosis of IBD. There were 10 cases of colonic inflammation initially diagnosed as UC. Etiologies included drug-induced colitis secondary to checkpoint inhibitors for cancers, ocrelizumab for multiple sclerosis, and nintedanib for pulmonary fibrosis. There were cases of ischemic colitis, idiopathic myointimal hyperplasia of mesenteric veins, segmental colitis associated with diverticulosis, and diversion colitis. There were 8 cases of systemic diseases, diagnosed as Common Variable Immunodeficiency, sarcoidosis and vasculitis, including cases of Henoch – Schönlein purpura and CTLA4 haploinsufficiency with autoimmune infiltrates. There were 5 cases of ileal disorders, ultimately diagnosed as lymphoma, tuberculosis, Meckel's diverticulum, and appendiceal carcinoid all previously thought to be CD. There were small bowel mucosal disorders including collagenous sprue and autoimmune enteropathy, and 2 polyposis cases secondary to Cronkhite-Canada and juvenile polyposis syndromes. There were also cases thought to be penetrating complications of CD, including a case of abdominal actinomyces infection. Finally, there were 3 cases where no consensus diagnosis was made, with broad differential diagnoses including cryptogenic multifocal ulcerous stenosis enteritis. CONCLUSIONS: IBD mimics were found in 15% of cases presented at a global IBD webinar in a 3-year period. Clinicians should have a high level of suspicion and actively pursue alternative etiologies when patients do not respond as anticipated to IBD therapy and/or when the disease characteristics are not completely consistent with IBD. These non-IBD diagnoses will lead to a significant change in medical, surgical and pharmacological treatment approaches, which will impact total cost, unplanned care and quality. Our IBD Live conference has positively impacted the care of our patients, and magnified the importance of considering a broad differential for IBD "mimics."